Characterization of morphology of certain colistin resistant strains of acinetobacter baumannii and its impact on resistance and virulence profiles - Marwa Shokry Abdelaziz Hesham; Magdy Ali Amin; Neveen M. Saleh; Reham Samir Mohamed (Cairo : Marwa Shokry Abdelaziz Hesham, 2019)
Acinetobacter baumannii (A.baumannii) is an opportunistic pathogen, which is one of the most common causes of nosocomial infections in patients in the intensive care unit (ICU). The organism{u2019}s ability to acquire diverse mechanisms of resistance limits therapeutic agents and makes the infection with high difficulty to treat. Therefore, the outbreaks of multi-drug resistant (MDR) A. baumannii have become a critical challenge for common antibiotic treatments. In these MDR strains, colistin is often the only remaining treatment; owing to its favorable properties of rapid bacterial killing, narrow spectrum of activity, and its associated slow development of resistance. Unfortunately, colistin-resistant clinical isolates have already been reported in recent studies. In this study, we explore the impact of gaining colistin resistance on the susceptibility pattern, in addition to cell morphology and cell wall of different strains of A. baumannii and linking it to its genetic bases. Out of one hundred and ten clinical isolates collected from ICU patients, ninety-five s were confirmed to be A. baumannii by the presence of gene blaOXA-51 using conventional PCR
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Microbiology and Immunology
Issued also as CD
Keywords: Acinetobacter baumannii; LpxACD; PmrB